Pengaruh Online Customer Review Terhadap Keputusan Pembelian Jasa Kamar Studi Pada Pengguna Online Travel Agent di Rocky Plaza Hotel Kota Padang - Anugrah, Dinda Rizky; Pasaribu, Pasaribu (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This research was conducted based on the results of observations during pre-research during industrial field practice at Rocky Plaza Hotel Padang and the background of the problem of Online Customer Reviews that are still few, there are negative comments and room sales through Online Travel Agents are still low. This type of research is descriptive associative classified as causal associative research with a survey method that aims to see the influence of Online Customer Reviews (X) on Purchase Decisions (Y) through Online Travel Agents at Rocky Plaza Hotel Padang. This research was conducted based on observations during the industrial field experience at Rocky Plaza Hotel Padang, the authors found problems, namely the low sales of rooms through Online Travel Agents and the number of reviews contained on online travel agent sites is still relatively small. The number of samples in this study were 208 respondents using purposive sampling technique. Data collection in this study was obtained using questionnaires and google forms that have been compiled with a Likert scale. Technical analysis in this study is simple linear regression and the coefficient of determination. Based on the results of the study, it can be concluded that: (1) Online Customer Review (X) in the category of not agreeing (51%), (2) purchasing decisions (Y) in the category of agreeing (54.8%), (3) test results simple regression, the results of the regression coefficient equation are equal to. Based on the above equation, the regression coefficient is 0.659 with a sig value. 0.000 0.05. This means that every increase of 1 unit of Online Customer Review will increase by 0.659 units of purchasing decisions. For the results of the R Square value obtained at 0.749, it means that the effect of the X variable on Y is 74.9% and 25.1% is influenced by other factors..